Estudo de polimorfismos de genes de reparo do DNA em lesão de fita simples e sua associação com aspectos clínicos e laboratoriais de portadores de síndrome mielodisplásica - Santiago, Sabrina Pinheiro (2015)
Myelodysplastic Syndrome (MDS) is a group of clonal diseases of hematopoietic progenitor cells, characterized by peripheral cytopenia (s), dysplasia of one or more myeloid cell lines and increased risk of developing acute myeloid leukemia. The pathogenesis of SMD involves DNA damage in hematopoietic stem cells likely to be affected by single-stranded DNA damage and the Nucleotide Excision Repair (NER) as one of the main mechanisms to ensure the genomic stability of cells -trunk. This case-control study of candidate genes proposed to evaluate the association of the polymorphisms XPA rs1800975, XPC rs2228000, XPD rs1799793 and XPF rs1800067 with the clinical variables of patients with Myelodysplastic Syndrome. This analysis used real-time quantitative PCR as a technique for genotyping between bone marrow samples from 95 MDS patients from the Walter Cantídio University Hospital and peripheral blood samples from 94 healthy elderly volunteers. For the polymorphism XPC rs2228000, we obtained, in relation to hemoglobin, in the genotypic distribution, that the CT genotype is associated with a higher odds ratio of hemoglobin levels below 8.0 g / dL (p = 0.010, OR 3.385, CI 1.343- 8,529); (P = 0.027, OR 2.75, CI 1.125-6.722) and in the dominant heterozygosis model (p = 0.013). In the present study, the genotype CC was associated with a higher odds ratio of Hb ≥ 8g / dL in the dominance model , OR 3.333, CI: 1.293-8.591); In relation to neutrophil counts we have that the mutant TT genotype has a higher odds ratio of neutrophil counts below 800 / mm3 (p = 0.017, OR 8,750, CI 1,470-52,098), that the CC genotype is associated with the highest ratio (P = 0.032, OR 2,833, CI 1,096-7,327) and in the homozygous model (p = 0.013, OR 17,500, CI 1,828-167,558) and that the combination CC + CT Of the recessive model was also associated with a higher odds ratio of neutrophils ≥ 800 / mm³ (p = 0.025, OR 12,500, CI 1,381-113,177). We also found that for genotype XPD rs1799793 the GG genotype is associated with a lower odds ratio of SMD in the dominance model (p = 0.009, OR 0.445, CI 0.242-0.816) and in the dominant heterozygosis model (p = 0.010, OR 0.440 , IC 0.235-0.825), and the same genotype seems to have a lower odds ratio for bone marrow ring sideroblast counts ≥ 15% in three different models: genotype distribution (p = 0.027, OR 0.980, CI 0.013-0.768) , Dominance (p = 0.027, OR, 4,643, CI 1,195-18,034) and dominant heterozygosity (p = 0.022, OR 5,000, CI 1,265-19,762). We did not find a significant association between the XPF polymorphisms rs1800067 and XPA rs1800975 and the clinical variables for patients with MDS. This study suggests that polymorphisms of DNA repair genes by nucleotide excision are associated with clinical features of patients with myelodysplastic syndrome.